New types of nearly open sets in topological spaces and their applications - A. M. Mubaraki; M. A. El Safty (Journal of Taibah University for Science)
In the current study, the idea of [Formula: see text]-open sets is used to introduce some new types of nearly open sets in topological space, where [Formula: see text] and [Formula: see text], thereby illustrating some of their basic qualities and the links between them. Some characterizations, topological properties, mappings, and separation axioms of these new concepts are also presented.